Effects of a Meaning-Based Approach in Teaching the Tense System to Malay ESL College Students - Agus, Rianto (2003)
It is not uncommon to see Malay students at college level face difficulty in communicating their ideas effectively in written English. Their difficulties indicate their lack of mastery of important grammatical systems of the English language. Their inability to effectively convey ideas in written English may be because during their time of learning English, they have been mostly presented with direct instruction in communicative strategies and/or grammatical instructions that emphasize a relation of formal determination. In general, this study explored the effects of an instructional approach which integrated target formal features into meaning-based activities (termed Meaning- Based Approach-MBA) on the acquisition of the English tense system. Specifically, this study investigated four issues: (1) the effect of MBA on learners perfonnance in understanding messages conveyed by verbs of the tense system: (2) the effect of MBA on learners' perfonnance in using messages conveyed by verbs of the tense system in written production; (3) the effect of MBA on Lower and Higher Proficiency Students' (LPS and HPS) performance in understanding messages conveyed by verbs of the tense system; and (4) the effect of MBA on Lower and Higher Proficiency Students' (LPS and HPS) performance in using messages conveyed by verbs of the tense system. A quasi-experimental between groups design was used in which a pretest, a sixweek treatment on tense system, and a posttest were administered. This study was conducted at Kolej Legenda Langkawi (KLL)-a private Malaysian institute of higher learning located on Langkawi island, Kedah, Malaysia. The subjects of this study were Malay ESL students taking an English proficiency course. The treatment group was presented with the MBA and the control group received instruction which focused on target fonns in isolation (tenned Fonn-Based Approach-FBA). The collected data was tested for statistical significance by means of an analysis of covariance (ANCOV A) for the first and the second issues and t-test for the third and the fourth issues.